Pengaruh kemampuan diri dan kesiapan untuk berubah terhadap kinerja Karyawan Monahara Center of Borobudur Study Kabupaten Magelang - Muhdin (CV. Kurnia Grup, 2023)
This study aims to examine the effect of self-ability and readiness to change on work motivation and employee performance, examine the effect of work motivation on employee performance, and examine the stronger influence between self-ability and readiness to change on performance if mediated by work motivation. The research sample was 127 employees of Manohara Center of Borobudur Study in Magelang District. The statistical analysis tool used in this study is the Multiple Linear Regression Analysis and Path Analysis model. Based on the results of the study using Multiple Linear Regression Analysis and path analysis (Path Analysis) shows the results between that self-ability and readiness to change have a significant effect on employee work motivation, self-ability has a significant influence on employee performance, while readiness to change does not have a significant effect on performance, work motivation has a significant influence on employee performance.